The Impact of E-Commerce and Accounting Information Systems on Entrepreneurial Decision-Making in MSMEs: A Quantitative Study in the Digital Era - Siswanto, Edy; Aqdam, Ahmad Ashifuddin (University of Science and Computer Technology, 2024)
This study investigates the influence of e-commerce and accounting information systems (AIS) on entrepreneurial decision-making among Micro, Small, and Medium Enterprises (MSMEs) in the digital era. Using a quantitative research approach, the study employs multiple linear regression analysis to examine the extent to which these technologies enhance data-driven decision-making. The findings reveal a significant positive relationship between e-commerce and AIS and the quality of decisions made by MSME operators. E-commerce provides real-time market insights, enabling faster responses to consumer trends, while AIS enhances financial accuracy and strategic planning by integrating financial data. Statistical analysis demonstrates that e-commerce and AIS collectively explain 66% of the variance in decision-making quality, with e-commerce contributing a regression coefficient of 0.45 and AIS at 0.55, both significant at p < 0.05. These technologies have enabled MSMEs to improve operational efficiency, respond promptly to market demands, and make more informed strategic decisions. However, barriers such as limited financial resources, technical expertise, and data security concerns pose challenges to broader adoption. The study emphasizes the necessity for government and institutional support in providing training and financial incentives to facilitate technology adoption among MSMEs. The findings contribute to the growing literature on digital transformation in business, highlighting the critical role of technology integration in enhancing decision-making processes in the MSME sector.